The Challenges of Intra-Party Conflicts in the All Progressive Congress in Ogun State, Nigeria - Adebajo, Adeola Aderayo; Olaide , Bello Wasiu; Rebecca, Ogundola Blessing (Kashere Journal of Politics and International Relations, 2025)
Intra-party conflicts among political parties have constituted a serious concern to democratic development in Nigeria. Rather than political parties being the strong bedrocks of democracy, their activities have affected democratic development in all ramifications. The All Progressives Party in Ogun State is not exempted from the internal party crisis affecting other political parties. In order to have a deeper understanding of the phenomenon, the paper interrogated intra-party conflict in the All Progressive Congress Chapter in Ogun state. The desk research method was used to obtain secondary data. The Realistic Group Conflict Theory (RGCT) was used as a theoretical framework. The paper argued that intra-party conflicts in the All Progressive Congress (APC) in Ogun state were primarily driven by factional and tribal-related interests, while leadership crisis, lack of internal democracy, monetization of democratic processes, and god-fatherism aggravated the crisis. Also, it further maintained that lack of coherent party ideology, egoistic and selfish ambitions of political leaders caused conflict in the party. In addition, the zero-sum approach to political succession and fragmented leadership styles contributed to the crisis in the party. It therefore recommended that winners- take all ambition and coercive leadership style should be discouraged in order to uphold unity of purpose in the party. The misuse of power of incumbency should be discouraged through strong institutional measures to curb further factionalization. The party leaders need to embrace alternative dispute resolution in addressing party crises by acquiring skills in different conflict management styles through professional training programmes.